Sistem Penunjang Keputusan Seleksi Calon Karyawan Terbaik Dengan Metode SMART Berbasis Dekstop - Sudiro, Achmad (Jurnal Ilmu Komputer, 2023)
The Simple Multi-Attribute Rating Technique (SMART) method is a multi-attribute decision making method that can be used to support decision makers in selecting several alternatives. In the process, the SMART method uses an adaptive linear model to assess each alternative. The assessment process for selecting the best employee candidates that is currently being given is still subjective, only taking into account the amount of craft work done in one month, other aspects have not been included in the assessment, this is because currently there is no longer any media that processes employee assessments in detail. This decision support system is expected to help decision makers in giving awards to the best employees.